Non-original & original visible spare parts for complex goods in the automotive industry under the intellectual property law of the European Union - Kocherzhenko, Arina (Riga Graduate School of Law, 2023)
This bachelor's thesis is aimed at analysing the current Community designs regulation 6/2002 of intellectual property law for the production and sale of automotive spare parts in the European Union and their preparedness for the changes associated with the right to repair legal initiative and manufacture technology using 3D printing. The study examines the legislation of the European Union as related to the protection of spare parts including the proposals for improving and liberalising the repair clause in the Community designs regulation 6/2002 and the national law of the European Union Member States. The study focuses on the repair term and repair clause as analysed from the comments and decisions of the Court of Justice of the European Union on the Acacia cases and the Monz Handelsgesellschaft case. The result of the research of Community designs regulation 6/2002 in the European Union and 35 U.S. Code § 171 - Patents for designs in the United States found the main similarity that both legal systems that design law protection do not include the protection of parts that perform purely technical tasks and difference that in the United States the courts rely on the doctrine of functionality and the doctrine of exhaustion as well as on case law, however, without having a repair clause in the Patents for designs 35 U.S.Code. The right-to-repair legal initiative in the European Union Circular Economy Action Plan aims to further develop the protection of spare parts with a focus on a green economy and improve the repair ability of complex goods. However, the current Community designs regulation 6/2002 is not ready for such a change, since the repair clause has not yet been harmonised and introduced into the national law of all member states of the European Union.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Research Subject Categories::LAW/JURISPRUDENCE::Private law::Intellectual property law; additive manufacturing; right to repair